Effects of mental fatigue on physical performance during prolonged intermittent sprinting - Coutts, A. J.; Smith, M.; Marcora, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Mental fatigue has been shown to impair performance during constant-power exercise, however its effects on performance during freely paced exercise are yet to be examined. The purpose of this study was to examine the influence of induced mental fatigue on performance during prolonged, intermittent sprinting. Furthermore, the study aimed to investigate the physiological and psychological factors that underpin any potential changes. Methods: In this single blind, randomized, crossover study, eight team sport athletes (age: 21 ±2 y, stature: 182 ±4 cm, body mass: 76 ±6 kg, VO2max 47 ±4 ml/kg/min) completed a 45-min intermittent running protocol that simulated typical team activity demands on a non-motorised treadmill on two separate occasions, following either 90-min of demanding mental activity (mental fatigue) or 90-min of emotionally neutral documentaries (control). The 45-min protocol consisted of one 3-min block repeated 15 times to allow for data comparison. Velocity and distance were measured at a frequency of 10 Hz throughout the protocol and analysed in 3-min blocks. Heart rate (HR) and oxygen consumption were recorded as 5-s averages while blood glucose and lactate concentrations were measured every 9 min. All physiological variables were analysed in 9-min blocks. Rating of perceived exertion (RPE) was measured every 5-min using a CR-100 scale. The effects of condition on all variables were tested using two-way repeated-measures ANOVA. Results: The demanding cognitive task increased mental fatigue (P<0.05), which caused a reduction in velocity of lower intensity activities (LIA) (P<0.001) while higher intensity activities and peak sprint velocity were not different between conditions. A condition × time interaction effect was also observed for LIA velocity (P=0.003). Mean oxygen consumption and HR were lower in the mental fatigue condition (oxygen consumption: 34 ±4.9 ml/kg/min; HR: 158 ±15.8 bpm) when compared with the control condition (oxygen consumption: 36 ±4.0 ml/kg/min; HR: 160 ±11.9 bpm; P<0.001), while blood glucose and lactate concentrations were not affected by mental fatigue. When normalised to velocity, RPE was higher in the mental fatigue condition (P=0.027). Discussion: Mental fatigue impairs performance during prolonged intermittent running. This is primarily observed as a reduction in LIA velocity. It appears that this reduction in performance is not mediated through physiological mechanisms but rather the athletes perceived exertion. Future studies should explore this relationship between mental fatigue and physical performance further.